Performance of prognostic scores in predicting long-term outcome following resection of colorectal liver metastases. Issue 7 (12th May 2014) - Roberts, K J; White, A; Cockbain, A; Hodson, J; Hidalgo, E; Toogood, G J; Lodge, J P A
Abstract: Background: Ten-year survival appears to define cure following resection of colorectal liver metastases (CRLMs). Various scores exist to predict outcome at 5 years. This study applied several scores to a patient cohort with 10 years of actual follow-up to assess their performance beyond 5 years. Methods: The study included consecutive patients who underwent liver resection at a single institution between 1992 and 2001. The ability of eight prognostic scoring systems to predict disease-free (DFS) and disease-specific (DSS) survival was analysed using the C-statistic. Results: Among 286 patients, the 1-, 3-, 5- and 10-year actual DSS rates were 86·6, 58·3, 39·5 and 24·5 per cent respectively. Seventy patients underwent 105 further resections for recurrent disease, of which 84·8 per cent were within 5 years of follow-up. Analysis of C-statistics showed only one score – the Rees postoperative index – to be a significant predictor of DFS and DSS at all time points. The remaining scores performed less well, and regularly showed no significant improvement in predictive accuracy over what would be expected by chance alone. No score yielded a C-statistic in excess of 0·8 at any time point. Conclusion: Although available risk scores can predict DFS and DSS, none does so with sufficient discriminatory accuracy to identify all episodes of recurrent disease. A non-negligible proportion of patients develop recurrent disease beyond 5 years of follow-up and so surveillance beyond this point may be advantageous. Abstract : None of them is perfect